Pulsed photoinitiated fabrication of inkjet printed titanium dioxide/reduced graphene oxide nanocomposite thin films. (29th May 2018) - Bourgeois, Briley; Luo, Sijun; Riggs, Brian; Ji, Yaping; Adireddy, Shiva; Schroder, Kurt; Farnsworth, Stan; Chrisey, Douglas; Escarra, Matthew
Abstract: This work reports a new technique for scalable and low-temperature processing of nanostructured TiO2 thin films, allowing for practical manufacturing of TiO2 -based devices such as perovskite solar cells at low-temperature or on flexible substrates. Dual layers of dense and mesoporous TiO2 /graphitic oxide nanocomposite films are synthesized simultaneously using inkjet printing and pulsed photonic irradiation. Investigation of process parameters including precursor concentration (10–20 wt%) and exposure fluence (4.5–8.5 J cm −2 ) reveals control over crystalline quality, graphitic oxide phase, film thickness, dendrite density, and optical properties. Raman spectroscopy shows the E g peak, characteristic of anatase phase titania, increases in intensity with higher photonic irradiation fluence, suggesting increased crystallinity through higher fluence processing. Film thickness and dendrite density is shown to increase with precursor concentration in the printed ink. The dense base layer thickness was controlled between 20 and 80 nm. The refractive index of the films is determined by ellipsometry to be 1.92 ± 0.08 at 650 nm. Films exhibit an energy weighted optical transparency of 91.1%, in comparison to 91.3% of a thermally processed film, when in situ carbon materials were removed. Transmission and diffuse reflectance are used to determine optical band gaps of the films ranging from 2.98 to 3.38 eV in accordance with the photonic irradiation fluence and suggests tunability of TiO2 phase composition. The sheet resistance of the synthesized films is measured to be 14.54 ± 1.11 Ω/□ and 28.90 ± 2.24 Ω/□ for films as-processed and after carbon removal, respectively, which is comparable to high temperature processed TiO2 thin films. The studied electrical and optical properties of the light processed films show comparable results to traditionally processed TiO2 while offering the distinct advantages of scalable manufacturing, low-temperature processing, simultaneous bilayer fabrication, and in situ formation of removable carbon nanocomposites.